Fragmentation patterns of 4(5)-nitroimidazole and 1-methyl-5-nitroimidazole - The effect of the methylation - E. Itälä; K. Tanzer; S. Granroth; K. Kooser; S. Denifl; E. Kukk (WILEY, 2022)
We present here the photofragmentation patterns of doubly ionized 4(5)-nitroimidazole and 1-methyl-5-nitroimidazole. The doubly ionized state was created by core ionizing the C 1s orbitals of the samples, rapidly followed by Auger decay. Due to the recent development of nitroimidazole-based radiosensitizing drugs, core ionization was selected as it represents the very same processes taking place under the irradiation with medical X-rays. In addition to the fragmentation patterns of the sample, we study the effects of methylation on the fragmentation patterns of nitroimidazoles. We found that methylation alters the fragmentation significantly, especially the charge distribution between the final fragments. The most characteristic feature of the methylation is that it effectively quenches the production of NO and NO+, widely regarded as key radicals in the chemistry of radiosensitization by the nitroimidazoles.